Bruch Membrane Opening Minimum Rim Width in Neuromyelitis Optica. Issue 1 (1st March 2022) - Bechet, Lorane; Cabre, Philippe; Merle, Harold
Abstract : Background: Optical coherence tomography (OCT) analyzes the neurodegeneration in neuromyelitis optica (NMO) and multiple sclerosis (MS) and quantifies optical atrophy. The retinal nerve fiber layer (RNFL) and ganglion cell layer (GCL) thickness are decreased, and this structural change is correlated with visual function of patients, including contrast vision and visual field deviation. The main objective of this study was to evaluate the Bruch membrane opening minimum rim width (BMO) of the patients with NMO. Methods: We studied the thickness of the BMO by OCT, in patients with NMO (n = 25; 34 eyes), MS (n = 50; 70 eyes), and a control group (n = 51; 100 eyes). The study evaluated the structure–function relationship with the correlation between OCT and visual function: Visual acuity, Pelli–Robson score, Sloan 2.5 and 1.25, color vision, standard automated perimetry (SAP), and frequency-doubling technology perimetry (FDT). Results: The average thickness of BMO was significantly reduced in NMO and MS with or without a history of optic neuritis (ON). Significant thinning of the average, nasal, and inferonasal BMO in the absence of ON in NMO was found compared with controls ( P = 0.022, 0.006, and 0.026, respectively). BMO was strongly correlated with Pelli–Robson score ( P < 0.001), Sloan 2.5 ( P < 0.001), and mean deviation of SAP and FDT ( P = 0.004). The sectorial study found a high correlation between the BMO and the corresponding sector of the visual field. Conclusions: The BMO thickness is decreased after ON in NMO and MS. This study showed an improved ability of BMO over RNFL and GCL to detect infraclinical impairment in patients with NMO without a history of optic neuropathy. Like the RNFL and GCL, BMO is well correlated with visual function, including contrast vision and visual field deviation.